MOTIVATION TO ACHIEVE SUCCESS IN HIGHER EDUCATION AMONG THE CHILDREN OF MOTORCYCLE TAXI DRIVERS IN OMBAY VILLAGE - Wasti S. Ur; Alboin Selly; Fredrik Abia Kande (Penelitian dan Pengembangan Ilmu, 2026)
The purpose of this study is to describe the motivation of motorcycle taxi drivers’ children to pursue higher education, to analyze the obstacles they face during their education, and to uncover the life lessons they learn in sustaining their studies. The method used is descriptive with a qualitative approach, using interviews and documentation techniques. The data sources for this study were five motorcycle taxi drivers’ children who were currently pursuing or had completed higher education, as well as their parents (motorcycle taxi drivers) who served as supporting informants. The results of this study indicate that the motivation to achieve success in higher education among motorcycle taxi drivers’ children is divided into two main forms: internal motivation and external motivation. Internal motivation includes the desire to change the family’s fate, the aspiration to obtain a better job, and the drive to make parents proud. Meanwhile, external motivation stems from family moral support, teacher encouragement, a positive social environment, and scholarships. The main supporting factors for success in higher education are family support, access to educational information, and educational assistance programs. Inhibiting factors identified include economic constraints, limited learning facilities, and social pressure to immediately work to support the family. Life lessons learned include the values of hard work, perseverance, discipline, and time management in the face of economic constraints; a never-give-up attitude in the face of academic obstacles and social pressures; and a growing sense of responsibility, independence, and commitment to completing higher education. These values shape a resilient character and strengthen motivation to achieve success in higher education. Supporting factors for success in higher education include family support, access to educational information, and educational assistance programs. Inhibiting factors include economic constraints, limited learning facilities, and social pressures to immediately work to support the family.